Fact-checking of health information on social networking sites: The moderating role of gender - Jiabei Xia; Tailai Wu; Zhuo Chen; Liqin Zhou (Digital Health)
Background This study aims to explore the factors related to fact-checking health information and the moderating role of gender on the effects of explored factors. Based on social cognitive theory (SCT) and social role theory (SRT), we established a research model to explore the factors of fact-checking on health information and the role of gender. Methods To validate the research model, data were collected by survey method and analyzed by partial least squares technique. Results The analysis results present that personal factors (self-efficacy and outcome expectancy), and environmental factors (perceived skepticism and perceived ambiguity) have significant impacts on fact-checking about health information. Meanwhile, our results reveal that gender moderates the effects of outcome expectancy, perceived skepticism, and perceived ambiguity on users’ fact-checking. Conclusion Our study uses SCT to explore the factors impacting fact-checking, while we combine it with SRT to understand the gender differences in the process of fact-checking health information in social networking sites.